2016
DOI: 10.1111/jnc.13737
|View full text |Cite
|
Sign up to set email alerts
|

Genotype differences in anxiety and fear learning and memory of WT and ApoE4 mice associated with enhanced generation of hippocampal reactive oxygen species

Abstract: Apolipoprotein E (apoE), involved in cholesterol and lipid metabolism, also influences cognitive function and injury repair. In humans, apoE is expressed in three isoforms. E4 is a risk factor for age-related cognitive decline and Alzheimer’s disease, particularly in women. E4 might also be a risk factor for developing behavioral and cognitive changes following 56Fe irradiation, a component of the space environment astronauts are exposed to during missions. These changes might be related to enhanced generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…Greater hippocampal atrophy and volume loss in ε4 carriers may also contribute to deficits in memory for fear extinction (den Heijer et al., ; Fanselow, ; Pievani et al, ), which can maintain re‐experiencing/intrusion symptoms. Villasana, Weber, Akinyeke, and Raber () found that mice carrying the ε4 allele had higher levels of heme oxygenase‐1, a marker of stress, in the hippocampus, and also exhibited greater anxiety‐related behaviors and conditioned fear responding. These findings suggest a possible mechanism linking ε4 carriage and intrusive symptoms among highly trauma‐exposed veterans.…”
Section: Discussionmentioning
confidence: 99%
“…Greater hippocampal atrophy and volume loss in ε4 carriers may also contribute to deficits in memory for fear extinction (den Heijer et al., ; Fanselow, ; Pievani et al, ), which can maintain re‐experiencing/intrusion symptoms. Villasana, Weber, Akinyeke, and Raber () found that mice carrying the ε4 allele had higher levels of heme oxygenase‐1, a marker of stress, in the hippocampus, and also exhibited greater anxiety‐related behaviors and conditioned fear responding. These findings suggest a possible mechanism linking ε4 carriage and intrusive symptoms among highly trauma‐exposed veterans.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral analysis was performed on 4–5 month-old animals (N= WT/PLK2 WT 11, WT/PLK2 Het 7, Syn-GFP/PLK2 WT 15, Syn-GFP/PLK2 Het 6, Syn-GFP/PLK2 KO 11 animals). Open field, novel object, rotarod, Morris water maze, contextual and cued fear conditioning behavior measures were performed as previously published ( 55 ).…”
Section: Methodsmentioning
confidence: 99%
“…The presence ApoE4 has been shown to be associated with increased oxidative stress in the brains of affected animals 19 . We evaluated the total ApoE concentration in the CSF of young males with cALD and found a mean of 17 µg/mL, consistent within the range of previously published results 2022 (Fig.…”
Section: Resultsmentioning
confidence: 99%